A Comparative Study on Effects of Defect Closure versus Non-Closure on Outcomes of Laparoscopic Direct Inguinal Hernia Repair - Subedi, Sushil Sharma; Kumar, Nishant; Acharya, Sabanam; Neupane, Durga Prasad (Nepal Journal of Medical Sciences, 2024)
Introduction: Laparoscopic direct inguinal hernia repair is a common surgical procedure with varying approaches to defect management. This study investigates the impact of defect closure versus non-closure on postoperative outcomes in this procedure. Defect closure, involving suturing the hernia defect, is often debated against non-closure, where the defect is left open. Understanding the differences in outcomes such as recurrence rates, postoperative pain, and recovery times is crucial for optimizing surgical techniques. This comparative analysis aims to provide insights into which method offers superior results, potentially guiding best practices in laparoscopic hernia repair and improving patient outcomes. Methods: It was a cross-sectional descriptive study conducted in B. P. Koirala Institute of Health Sciences, Dharan. Two groups were created using purposive alternate number sampling technique with 44 in each defect closure and non-closure group. Results: Forty-four patients were enrolled in each cohort. No significant differences were observed between the two patient populations' demographic information and the mean operative time. Compared to the group that did not undergo direct defect closure, the group that had direct defect closure demonstrated reduced seroma formation (24% versus 33%, p = 0.225) at 1st week, though it resolved in both groups on 6 months follow-up. The mean difference in postoperative hospital stay between these two groups was not statistically significant (1.16±0.420 and1.2±0.447, p=0.661). There was no evidence of recurrence in either group during 1 year follow up and also there was no significant chronic pain in either of the group. Conclusions: Our study shows that there was no statistical difference between defect closure and non-closure groups with regard to postoperative pain, vessel injury, vascular injury, peritoneal tear, seroma formation, chronic pain and recurrence rate. Randomized controlled trials will be required to further evaluate these outcomes.